Analisis Struktur Dramatik Freytag Dalam Film 172 Days Karya Nadzira Shafa - Kurnia Widiawati; Etty Umamy; Khoirul Efendiy (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2026)
172 Days, a film by Nadzira Shafa, is a religious film based on a true story that depicts the spiritual and emotional journey of its main character through a well-structured narrative. This study aims to describe and analyze the application of Freytag’s dramatic structure in the film’s storyline, which consists of five main stages: exposition, rising action, climax, falling action, and resolution. A descriptive qualitative approach was employed, using Miles and Huberman’s data analysis model to explore the narrative construction in the film. The results reveal that each stage of Freytag’s structure is clearly identifiable and cohesively forms a dramatic sequence, portraying Zira’s transformation from a spiritually fragile woman into a mature, faithful, and resilient individual. The exposition presents the emotional roots of the conflict, the rising action illustrates the hijrah process and Zira’s meeting with Ameer, the climax portrays the peak of happiness in marriage, the falling action shows the struggle with illness, and the resolution conveys a profound sense of loss and life meaning. The findings conclude that Freytag’s structure is effective for analyzing true-story films with strong religious values. This study contributes to the development of narrative film analysis, particularly in religious cinema, and may serve as a reference for filmmakers in crafting emotionally resonant and meaningful storylines.